Polybutylene terephthalate on metals: A density functional theory and cluster models investigation - David, Melanie (Animo Repository, 2006)
The strength of adhesion of polybutylene terephthalate (PBT) on aluminium is investigated using density functional theory-based energy calculations. The aluminium atom is connected to a PBT monomer at different orientations, and total energies are calculated and compared to determine the most stable orientation. The binding is strongest when the Al is oriented at 180° to the ester group of the monomer. Using this orientation as a basis, PBT adhesion on Ti, Ag, and Au is also investigated. © 2006 IOP Publishing Ltd.